Financial and Managerial Accounting. - Weygandt, Jerry J.; Kieso, Donald E.; Kimmel, Paul D. (Hoboken : John Wiley Inc, 2015)
Financial and Managerial Accounting, 2nd Edition provides students with a clear introduction to fundamental accounting concepts.  The Second Edition helps students get the most out of their accounting course by making practice simple.  Both in the print text and online in WileyPLUS with ORION new opportunities for self-guided practice allow students to check their knowledge of accounting concepts, skills, and problem solving techniques and receive personalized feedback at the question, learning objective, and course level.  Newly streamlined learning objectives help students use their study time efficiently by creating a clear connections between the reading and video content, and the practice, homework, and assessments questions. Weygandt, Financial and Managerial Accounting is ideal for a two-semester Financial and Managerial Accounting sequence where students spend equal time learning financial and managerial accounting concepts, and learn the accounting cycle from a corporate perspective.  This program begins by introducing students to the building blocks of the accounting cycle and builds to financial statements. WileyPLUS with ORION sold separately from the text.
LO 4: Analyze the effects of business transactions on the accounting equation.Transaction Analysis; Summary of Transactions; LO 5: Describe the four financial statements and how they are prepared.; Income Statement; Retained Earnings Statement; Balance Sheet; Statement of Cash Flows; LO *6: APPENDIX 1A: Explain the career opportunities in accounting.; Public Accounting
Electronic reproduction.
Keywords: Accounting; Electronic books